Telemedicine during and post-COVID 19: The insights of neurosurgery patients and physicians. (May 2022) - El Naamani, Kareem; Abbas, Rawad; Mukhtar, Sarah; El Fadel, Omar; Sathe, Anish; Kazan, Adina S.; El Hajjar, Rayan; Sioutas, Georgios S.; Tjoumakaris, Stavropoula I.; Menachem Maimonides Bhaskar, Sonu; Herial, Nabeel A.; Gooch, Michael R.; et al.
Highlights: COVID-19 has caused massive surge in telemedicine utilization as patients and physicians tried to minimize in-person contact to halt impact of the pandemic. For patients, the main disadvantage of telemedicine was its technical difficulty, but the majority were satisfied with their telemedical experience compared to clinic visits. For physicians, the main disadvantage of telemedicine was the inability to perform a physical exam. Both patients and physicians believed that telemedicine should remain as an option even after the COVID-19 pandemic is over. Abstract: Objective: COVID-19 has caused a massive surge in telemedicine utilization as patients and physicians tried to minimize in-person contact to avoid the spread and impact of the pandemic. This study aims to expand on the knowledge of telemedicine during and beyond the COVID-19 era as it pertains to its use, efficacy, and patient and provider satisfaction through surveys. Methods: This is a retrospective study involving 93 patients and 33 Neurosurgery physicians who anonymously participated in the survey about their experience with telemedicine visits. Results: Most respondents indicated extreme satisfaction with their telemedicine encounters during the pandemic (77%). As for how comfortable physicians are in providing a diagnosis via telemedicine compared to clinic visits, 7 (21.9%) physicians felt extremely comfortable, 13 (40.6%) felt somewhat comfortable, 2 (6.4%) were neutral, 9 (28.1%) felt somewhat uncomfortable and 1 (3.1%) felt extremely uncomfortable. Physical examination was the main tool that telemedicine didn't provide (n = 21, 100%). Conclusion: Telemedicine has become a major force in the health care system under the circumstances the world is witnessing. Physicians and patients have displayed high levels of satisfaction with telemedicine which could be pivotal to improving healthcare access to underprivileged areas beyond the pandemic.